The histone chaperoning pathway: from ribosome to nucleosome. Issue 1 (22nd March 2019) - Pardal, Alonso J.; Fernandes-Duarte, Filipe; Bowman, Andrew J.
Abstract : Nucleosomes represent the fundamental repeating unit of eukaryotic DNA, and comprise eight core histones around which DNA is wrapped in nearly two superhelical turns. Histones do not have the intrinsic ability to form nucleosomes; rather, they require an extensive repertoire of interacting proteins collectively known as 'histone chaperones'. At a fundamental level, it is believed that histone chaperones guide the assembly of nucleosomes through preventing non-productive charge-based aggregates between the basic histones and acidic cellular components. At a broader level, histone chaperones influence almost all aspects of chromatin biology, regulating histone supply and demand, governing histone variant deposition, maintaining functional chromatin domains and being co-factors for histone post-translational modifications, to name a few. In this essay we review recent structural insights into histone-chaperone interactions, explore evidence for the existence of a histone chaperoning 'pathway' and reconcile how such histone-chaperone interactions may function thermodynamically to assemble nucleosomes and maintain chromatin homeostasis.